Avaliação da viabilidade técnica, econômica e ambiental da produção de piso intertravado com agregado da concha de sururu - Tenório, Arthur Amaral Batista (2023)
In this study, the sustainable reuse of Sururu shells (Mytella falcata) in civil construction was explored, highlighting not only the approach to environmental problems resulting from inadequate disposal, but also the promotion of local partnerships that generate jobs and boost the regional economy. The present invention consisted of analyzing the interlocking floor with partial replacement of the fine aggregate (natural medium sand) with grains of Sururu shells. A sustainable approach was sought, analyzing technical, economic and environmental feasibility. Detailed physicochemical analyzes were carried out, including Granulometry, X-ray Fluorescence (XRF), X-ray Diffraction (XRD) and Thermogravimetric Analysis (ATG), to characterize the properties of the shells. When defining the concrete mix, a volume ratio of 1:2.33:0.37:2.00:0.43 (cement: sand: crushed stone powder: crushed stone 0: water) was established. Various sand replacement formulations were also examined, varying between 2.5%, 5.0%, 7.5% and 10.0%. During laboratory tests, the results met technical specifications favorably. The C-5% composition presented a compressive strength of 37.87 MPa, meeting the technical requirements established by the standard for concrete pieces intended for paving, which requires resistance equal to or greater than 35 MPa. Water absorption tests demonstrated effectiveness in promoting adequate drainage, with water absorption variations within the acceptable range, remaining below 0.77%. These results highlighted the potential of Sururu shells as a source of technical, economic and environmental interest in the manufacture of interlocking pavements. This study not only contributed to the development of innovative technical materials in the interlocking flooring market, but also emphasized the importance of sustainable practices in construction and reinforces the Circular Economy.